ANALYSIS OF INFLUENCE OF FINANCIAL FACTORS ON CASH HOLDINGS OF NON-FINANCIAL COMPANIES - Siauwijaya, Rahmat; Putri, Shinta (Bina Nusantara University, 2024)
This study investigates the influence of several factors on company cash holdings, including market to book ratio, net working capital, liquidity, company size, and cash flow. It utilizes a balanced panel dataset consisting of 80 non-financial companies in the property and real estate sector listed on the Indonesia Stock Exchange during the period of 2010-2021. The research sample was selected based on specific criteria, resulting in a total of 33 companies. The findings indicate that the market to book ratio variable has a significant differential impact on cash holdings between companies with high and low levels of cash holdings. Additionally, net working capital and company size also exhibit significant effects on cash holdings, while liquidity does not have a significant influence on companies with high cash holdings. These findings provide valuable insights for corporate management and financial regulators in managing company cash and making financial decisions. The practical implication underscores the importance of effective cash management and transparency in financial practices for sustainable business growth.